2007
DOI: 10.1002/da.20176
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of paroxetine for chronic PTSD, dissociation, and interpersonal problems in mostly minority adults

Abstract: This study evaluated the efficacy of paroxetine for symptoms and associated features of chronic posttraumatic stress disorder (PTSD), interpersonal problems, and dissociative symptoms in an urban population of mostly minority adults. Adult outpatients with a primary DSM-IV diagnosis of chronic PTSD received 1 week of single-blind placebo (N = 70). Those not rated as significantly improved were then randomly assigned to placebo (N = 27) or paroxetine (N = 25) for 10 weeks, with a flexible dosage design (maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 44 publications
0
42
0
1
Order By: Relevance
“…In a later study involving 70 people with chronic PTSD, Marshall et al (2007) found significantly different response rates of 67% for paroxetine v. 27% for placebo after 10 weeks. Exposure therapy (a form of CBT) plus paroxetine has been found superior in producing remission compared with exposure therapy plus placebo (Schneier 2012).…”
Section: Antidepressantsmentioning
confidence: 92%
“…In a later study involving 70 people with chronic PTSD, Marshall et al (2007) found significantly different response rates of 67% for paroxetine v. 27% for placebo after 10 weeks. Exposure therapy (a form of CBT) plus paroxetine has been found superior in producing remission compared with exposure therapy plus placebo (Schneier 2012).…”
Section: Antidepressantsmentioning
confidence: 92%
“…As with sertraline, the beneficial effects of paroxetine were noticeable at week 4 (Tucker et al 2001) in one trial, and both trials showed evidence of significant improvement in measures of social and occupational function at endpoint. With the majority of previously published trials using primarily Caucasian populations, a more recent RCT by Marshall et al (2007) was able to demonstrate that the positive effects of paroxetine (up to 60 mg) extended to a sample with a high proportion of ethnic minorities (75%). Further, benefits of the medication were seen not only for core PTSD symptoms but also for dissociative symptoms and interpersonal problems, psychopathology that often accompanies this illness.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssris)mentioning
confidence: 93%
“…In 2010, the US Department of Veterans Affairs/Department of Defense (VA/DoD) Clinical Practice Guideline (CPG) for Management of PTSD established sertraline, paroxetine, and the selective serotonin-norepinephrine reuptake inhibitor (SNRI) venlafaxine as the first line pharmacological treatments for PTSD 36. These recommendations were established based on results from numerous randomized controlled trials (RCT) using SSRI/SNRIs, including sertraline,37,38 paroxetine,39 and venlafaxine 40. Although the evidence supports the use of SSRI/SNRIs for symptom reduction in PTSD, the overall effect sizes are modest 41,42.…”
Section: Pharmacological Treatments For Ptsdmentioning
confidence: 99%